Assessing the Economic Feasibility of Integrated Waste to Use Systems for Uganda - Agunyo, Miria Frances; Kizza-Nkambwe, Sarah; Bacwayo, Kukunda Elizabeth (The Global Environmental Engineers, 2021)
Waste and sanitation Management is a major challenge in urban areas in Uganda where waste is composed of atleast 70% organic content and is basically collected and disposed of in landfills. While 90% of the sanitation facilities used are onsite systems often requiring additional treatment of sewage and faecal matter sewage yet faecal and sewage sludge treatment plants are few. The projected population increase is expected to further influence urbanization, increasing the need for basic waste and sanitation services. Integrated Waste to Use systems that consider combined management of organic waste streams i.e. biowaste, animal waste, sewage and faecal sludge, could be a viable solution for the urban areas. The systems which consist of a combination of anaerobic digestion, composting, incineration and solar drying technologies promote resource recovery in the form of biogas, briquettes and organic fertilizer. The economic feasibility of the Waste to Use systems was carried out and the results indicated that the feasibility of the systems was positively influenced by the inclusion of the anaerobic digestion process, which allowed for recovery of biogas and digestate as organic fertilizer. Furthermore, a combination of low system investment costs, increased revenues from resource recovery, consideration of equity capital of at least 30%, interest rate of at most 10% and fugitive emissions less than 7 % would positively influence the economic feasibility of the system alternatives.